Analysis of changes in flowering phases and airborne pollen dispersion of the genus Betula (birch) - Veriankaitė, Laura; Šaulienė, Ingrida; Bukantis, Arūnas (Journal of Environmental Engineering and Landscape Management, 2010)
The scientists evaluate the climate change by various methods. The long‐term phonological observation is a quite significant indicator of this phenomenon. Moreover, the forecasting of plants flowering period or changing of amount of pollen production is important for guarantying of social health. The aim of the research 0 to analyze the interdependence of flowering changes and pollen concentration under the climate change according to the long‐term phenological data and evaluation of aeropalynological situation in Lithuania. For this purpose one based upon the data of birch flowering (1970–1999) and birch flowering and pollen concentration in air (2004–2008). The interpretation of data with statistic methods showed that the start of birch flowering varies in different years (8–32 days) and the regional differences increase (approximately 3 days during 30 years). One phenological station does not reflect the real aerobiological situation in the observation site. Tight analysis of pollen and phenological data basing upon the flowering data allows gathering knowledge about possible change of the pollen seasons in future. Beržo genties žydėjimo fazių ir žiedadulkių sklaidos pokyčių analizė Santrauka. Klimato kaitą mokslininkai vertina įvairiais metodais. Labai reikšmingas šio reiškinio indikatorius – daugiamečių fenologinių stebėjimų duomenys. Augalų žydėjimo laiko ar žiedadulkių produkcijos kiekio pokyčio prognozavimas yra svarbus visuomenės sveikatai užtikrinti. Tyrimo tikslas – pagal ilgamečius fenologinius duomenis ir įvertinus aeropalinologinę situaciją Lietuvoje išanalizuoti žydėjimo pokyčių ir žiedadulkių koncentracijos tarpusavio priklausomumą vykstant klimato kaitai. Šiam tikslui remtasi beržo žydėjimo (1970–1999 m.) ir beržo žydėjimo bei žiedadulkių koncentracijos ore (2004–2008 m.) duomenimis. Duomenis interpretuojant statistiniais metodais nustatyta, kad beržo žydėjimo pradžia įvairiais metais varijuoja (8–32 dienos), ir didėja regioniniai skirtumai (apytiksliai 3 dienos per 30 metu). Viena fenologinė stotis neatspindi realios aerobiologinės situacijos stebėjimo vietoje. Glaudi žiedadulkių ir fenologinių duomenų analizė, remiantis žydėjimo duomenimis, leidžia daryti prielaidas apie galimą žiedadulkių sezonų kaitą ateityje. Reikšminiai žodžiai: Betula, žiedadulkės, žydėjimas, sklaida, klimato kaita, Lietuva, aeropalinologija, fenologija. Анализ изменений в цветении рода березы и дисперсии пыльцы Резюме. Для оценки изменения климата ученые используют различные методы. Значительным показателем этого явления являются многолетние фенологические наблюдения. Кроме того, прогнозирование времени цветения или изменения продукции пыльцы растений является важным этапом в управлении здравоохранением. Целью нашего исследования было на основании многолетних фенологических наблюдений и оценки аеропалинологической ситуации в Литве проанализировать взаимосвязь между изменением цветения и концентрацией пыльцы в воздухе в связи с изменением климата. Для этой цели были использованы данные цветения березы за период 1970– 1999 гг., цветения березы и данные концентраций пыльцы в воздухе, охватывающие период 2004–2008 гг. Благодаря применению статистических методов для интепретаций данныx, было установлено, что началo цветения березы колеблется из года в год (8–32 дня), увеличиваются региональные различия (около 3 дней за 30 лет). Показано, что одна фенологическая станция не отражает реальную аеропалинологическую ситуацию. Сравнительный фенологический и пыльцевой анализ, проведенный на основании данных цветения, свидетельствуeт о возможныx измененияx в пыльцeвыx сезонаx в будущем. Ключевые слова: Betula, пыльца, цветение, распространение, изменение климата, Литва, аеропалинология, фенология. First Publish Online: 27 Jun 2011